A monoclonal antibody against basic fibroblast growth factor attenuates cisplatin resistance in lung cancer by suppressing the epithelial-mesenchymal transition. (27th May 2022) - Hu, Penghui; So, Kaman; Chen, Hongjie; Lin, Qimou; Xu, Meng; Lin, Yiguang
Objectives : To investigate the underlying mechanisms of how the basic fibroblast growth factor monoclonal antibody (bFGFmAb) attenuates cisplatin (DDP) resistance in lung cancer using A549 cells and cisplatin-resistant A549 cells (A549/DDP). Methods : Cancer cell proliferation, cell viability, and 50% inhibitory concentration (IC50) of cisplatin were assessed. Transwell assays were utilized to evaluate the invasion activity of tumor cells in response to treatment. Epithelial-to-mesenchymal transition markers and drug resistance proteins were analysed using Western blots. Results: We demonstrate that the bFGFmAb inhibits the proliferation and invasion of both A549 and A549/DDP cells. The bFGFmAb increases cisplatin sensitivity of both A549 and A549/DDP cells as evidenced by an increase in the IC50 of cisplatin in A549 and A549/DDP cells. Furthermore, bFGFmAb significantly increases the expression of E-cadherin, whilst decreasing the expression of N-cadherin and bFGF in both cell lines, thereby showing inhibition of epithelial-to-mesenchymal transition. In addition, we demonstrate that bFGFmAb significantly reduces the expression of the lung resistance protein. Conclusions: Our data suggests that the humanized bFGFmAb is a promising agent to attenuate cisplatin resistance in NSCLC. The underlying mechanism for this effect of bFGFmAb may be associated with the inhibition of epithelial-to-mesenchymal transition and reduced expression of lung resistance protein.